The Use of Citrus Peel Bio-Pesticides Against the Mortality of Fire Ants (Solenopsis) on Rambutan Tree (Nephelium lappaceum) - Titah Nurul Lathifah T.; A. Assyifa Mappadeceng Okarniatif; Faradiba Bagenda; Sugira Selfi Yuniar; Salsabila Nurain; Rimawati A.I Sadarang; Muhammad Rusmin (Perkumpulan Dosen Muda (PDM) Bengkulu, 2022)
This article aims to explain how to manufacture and use bio-pesticides for citrus peels to control Plant Destruction Organisms (OPT) insects on plants. The research method used is an experimental method, namely by extracting the orange peel, then the extract is tested for its ability to kill pests. The time of the study was carried out on March 21 to 23, 2022. The results showed that bio-pesticides were quite effective in killing Plant Destruction Organisms (OPT) insects.